Pigs Weaned from Sows Fed a Feed Flavor Had Improved Nursery Performance, but Feed Flavor in the Nursery Diets did not Impact Performance - Mikayla S. Spinler; Jordan T. Gebhardt; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 360 weaned pigs (DNA 241 × 600: initially 12.6 lb) were used to evaluate the effects of previous sow feed flavoring treatment (control vs. flavor) and nursery diets formulated with or without a feed flavor on growth performance in a 38-d trial. Pigs were weaned at approximately 19 d from sows fed diets with or without 0.05% of the feed flavor (Krave AP, Adisseo, Alpharetta, GA). Pigs were placed in pens (5 to 6 pigs per pen) within sow treatment and were randomly assigned to 1 of 2 dietary nursery treatments. There were 14 to 17 replications per treatment. Nursery treatments were either a control diet or a diet containing a feed flavor (Delistart #NA 21, Adisseo, Alpharetta, GA) added at 0.05% of the diet. Dietary treatments were arranged in a 2 × 2 factorial with main effects of sow and nursery treatment. Offspring from sows fed the flavor diet had a higher (P<0.001) BW at weaning, which was maintained throughout the study. No significant differences were observed for ADG, ADFI, or F/G during phase 1. During phase 2, there was a tendency (P<0.10) for a main effect of both nursery and sow diet on ADG. Pigs from sows fed the flavor diet had greater ADG compared to pigs from sows fed the control diet, and pigs fed the control diet had increased ADG compared to those fed the flavor diet. During phase 2, there was a tendency (P<0.10) observed for a main effect of sow treatment on ADFI, with pigs from sows fed the flavor diet having greater ADFI. During phase 3, there was a main effect (P<0.05) of nursery treatment on both ADFI and F/G where pigs fed the feed flavor diet had greater ADFI but poorer F/G. A tendency (P<0.10) was observed for an interaction between sow and nursery diet for ADG with pigs fed the flavor diet that were obtained from sows fed the flavor diet having greater ADG but no difference was observed when pigs were obtained from sows fed the control diet. Overall, progeny from sows fed a diet containing a feed flavor had greater ADG (P= 0.038) and ADFI (P= 0.043) and final BW (P<0.001) during the trial. In conclusion, offspring from sows fed a feed flavor had increased ADG, ADFI, and BW, but the presence of a feed flavor in the nursery did not elicit better overall nursery performance.
Keywords: feed flavor; nursery pig; lactation; sows